Efficacy of KFD-365-02 Rates and Mixtures in Imidazolinone-Tolerant Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2020)
This study compared various tank mixes of genericS-metolachlor/mesotrione and imazamox for weed control in imidazolinone-tolerant grain sorghum. All herbicides provided more than 90% control of Russian thistle, velvetleaf, and green foxtail, and kochia control late in the season was 85% or more. Puncturevine control late in the season was 80 to 90% with all herbicides except Coyote followed by KFD-365-02 and by KFD-365-02 at 6 oz/a plus atrazine followed by 2,4-D. Only Coyote followed by KFD-365-02 plus atrazine or 2,4-D controlled Palmer amaranth more than 78% late.
Keywords: herbicide-tolerant sorghum